2014
DOI: 10.2478/acve-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beta-glucan and vaccination against Lawsonia intracellularis on selected immune indices in weaned piglets

Abstract: The aim of this paper was to study the immunostimulating effects of feed additive containing beta-glucan given to pregnant sows and consecutive specific immunomodulation by vaccination of their suckling piglets. Thirty-five suckling piglets from the control and experimental group of sows were divided into four groups. Selected blood indices of immune profile (TIg, IMA, SI), specific antibodies against Lawsonia intracellularis formed in the blood serum of suckling piglets after vaccination, as well as productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This belief stemmed from the fact that L. Intracellularis infections are known to be endemic on the affected farms and are known to cause acute mortalities in this age group [11][12][13]. Our examinations results support these statements, because Lawsonia intracellularis was also detected.…”
Section: Results and Discusionsupporting
confidence: 81%
“…This belief stemmed from the fact that L. Intracellularis infections are known to be endemic on the affected farms and are known to cause acute mortalities in this age group [11][12][13]. Our examinations results support these statements, because Lawsonia intracellularis was also detected.…”
Section: Results and Discusionsupporting
confidence: 81%
“…Various infl uences which could impact colostral immunity were already described [21,22,23]. The current study showed that the IHC technique is a useful tool for detection, localisation and distribution of CSFV in formalin fi xed, paraffi n embedded tissue samples.…”
Section: Discussionmentioning
confidence: 88%
“…The transfer of maternal Hp to newborn piglets via colostrum was demonstrated [32]. The increasing levels of Hp in suckling piglets may have protective functions and play a role in the intrinsic defence mechanisms of newborn piglets if Hp plays a role in altering the T helper cells 1-2 balance to achieve immune homeostasis [33,41]. However, the direct transfer of Hp from colostrum to newborn calves was not demonstrated, which may be related to the different hepatic regulation of Hp production between calves and piglets [34].…”
Section: Discussionmentioning
confidence: 99%